Proceedings 12th International Conference on Advances in Steel-Concrete Composite Structures - ASCCS 2018 2018
DOI: 10.4995/asccs2018.2018.6959
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on demountable shear connectors in profiled composite slabs

Abstract: This paper presents an experimental study on demountable shear connectors in profiled composite slabs. Overall, three groups of push-off tests were conducted to assess the shear capacity, stiffness and ductility of the shear connectors. In all the specimens, a pair of shear studs were used per trough and were bolted to each side of the flange of a loading beam. Different concrete strength, embedment height of the shear studs and reinforcement cage were considered. Particularly, a joint was made between the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The full-scale composite beam test demonstrated that the ultimate moment capacity of a demountable beams can be well predicted by the plastic theory [30]. Furthermore, as push-out tests on threaded studs were conducted in both continuous and discontinuous metal decking composite slabs, it was established that connectors in continuous slabs had lower ultimate strength, but higher strength at 6 mm slip than those in discontinuous slabs [31].…”
Section: Bolt Diametermentioning
confidence: 89%
See 1 more Smart Citation
“…The full-scale composite beam test demonstrated that the ultimate moment capacity of a demountable beams can be well predicted by the plastic theory [30]. Furthermore, as push-out tests on threaded studs were conducted in both continuous and discontinuous metal decking composite slabs, it was established that connectors in continuous slabs had lower ultimate strength, but higher strength at 6 mm slip than those in discontinuous slabs [31].…”
Section: Bolt Diametermentioning
confidence: 89%
“…In this way, the final product has a geometry similar to the previously described bolts without embedded nuts. In past years, a series of tests followed by numerical simulations were conducted on these connectors installed in both solid slabs and composite slabs with metal decking [17,24,30,31,38]. Variations in the length of the threaded and collar part of the stud were covered by such studies, which also focused on concrete strength, reinforcement arrangement in push-out test set-up, shear connector height and temperature level during loading.…”
Section: Bolt Diametermentioning
confidence: 99%
“…One layer of Ø8 mm reinforcement was placed in the top zone of the slab. Longitudinal bars were bent on one side forming a hook to reinforce the supporting rib of the concrete slab, as suggested by some authors [24,25]. Stirrup bars applied in specimens of the series DLU were formed in a U-shape to pass around the headed stud.…”
Section: Fig 2 Configuration Of Push-out Specimensmentioning
confidence: 99%
“…Also, a system made of T-bolts and clamps was experimentally investigated [23]. Though most of the research has been focused on demountable shear connections in solid concrete slabs, some studies have investigated the behaviour of bolted shear connectors in composite slabs with profiled steel sheeting [19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%